Chemokines and lymphocyte homing in Sjögren’s syndrome - Liao, Jiahe; Yu, Xinbo; Huang, Ziwei; He, Qian; Yang, Jianying; Zhang, Yan; Chen, Jiaqi; Song, Weijiang; Luo, Jing; Tao, Qingwen (Frontiers in Immunology, 2024)
Sjögren's syndrome (SS) is a chronic systemic autoimmune disease that typically presents with lymphocyte, dendritic cell, and macrophage infiltration of exocrine gland ducts and the formation of ectopic germinal centers. The interactions of lymphocyte homing receptors and addressins and chemokines and their receptors, such as α4β7/MAdCAM-1, LFA-1/ICAM-1, CXCL13/CXCR5, CCL25/CCR9, CX3CL1/CX3CR1, play important roles in the migration of inflammatory cells to the focal glands and the promotion of ectopic germinal center formation in SS. A variety of molecules have been shown to be involved in lymphocyte homing, including tumor necrosis factor-α, interferon (IFN)-α, IFN-β, and B cell activating factor. This process mainly involves the Janus kinase-signal transducer and activator of transcription signaling pathway, lymphotoxin-β receptor pathway, and nuclear factor-κB signaling pathway. These findings have led to the development of antibodies to cell adhesion molecules, antagonists of chemokines and their receptors, compounds interfering with chemokine receptor signaling, and gene therapies targeting chemokines and their receptors, providing new targets for the treatment of SS in humans. The aim of this study was to explore the relationship between lymphocyte homing and the